2013
DOI: 10.1111/jre.12136
|View full text |Cite
|
Sign up to set email alerts
|

Deferoxamine promotes osteoblastic differentiation in human periodontal ligament cells via the nuclear factor erythroid 2‐related factor‐mediated antioxidant signaling pathway

Abstract: These data indicate, for the first time, that nontoxic DFO promotes osteoblastic differentiation of hPDLCs via modulation of the Nrf2-mediated antioxidant pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 65 publications
2
36
1
Order By: Relevance
“…27,28 In contrast, human periodontal ligament cells do not seem to be particularly sensitive to DFO, as even concentrations of up to 200 mM still exerted pro-osteogenic effects. 26 In our hands, DFO reduced human BMSC viability at similar concentrations as murine BMSC (i.e., 50 mM, data not shown). However, it should be noted that the impact on cell viability did not seem to be of biological significance, as osteoblasts treated with 50 mM still differentiate better than untreated cells.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…27,28 In contrast, human periodontal ligament cells do not seem to be particularly sensitive to DFO, as even concentrations of up to 200 mM still exerted pro-osteogenic effects. 26 In our hands, DFO reduced human BMSC viability at similar concentrations as murine BMSC (i.e., 50 mM, data not shown). However, it should be noted that the impact on cell viability did not seem to be of biological significance, as osteoblasts treated with 50 mM still differentiate better than untreated cells.…”
Section: Discussionmentioning
confidence: 52%
“…Our study is in line with a number of other studies that have shown an osteoblast-supporting effect of DFO. [26][27][28]44,45 Interestingly, osteoblasts treated with 50 mM DFO showed a somewhat decreased mineralization potential as compared to 25 mM DFO, indicating that this concentration might already exert toxic effects. In fact, we found a reduced cell viability in murine cells treated with 50 mM DFO, while cell vitality was not affected at 25 mM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baschant et al showed that attenuated osteogenic differentiation was observed in the presence of excess iron, whereas elevated osteogenic differentiation was observed in the presence of the iron chelator (DFO) [25]. Chung et al discovered that long-term treatment with 200 µM DFO could promote the mineralization of human periodontal ligament cells [16]. In the present study, we observed that short-term treatment with a low concentration of iron chelator (10 µM DFO) at the early stages of mineralization could promote the differentiation and mineralization of DPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Chung et al discovered that DFO treatment could promote the generation of Reactive Oxygen Species (ROS) through sequestering intracellular iron in normal cells [16]. It is well established that ROS is one prominent inducer for autophagy.…”
Section: Introductionmentioning
confidence: 99%